HAK HADHANAH DALAM PUTUSAN PENGADILAN AGAMA - Eli martati; Firdaus Firdaus (JURIS (Jurnal Ilmiah Syariah), 2018)
The purpose of the research is to reveal the rights of custody of children that have not been mumajiz if there is a divorce seen from the requirements set by the ulama in Islamic law or the benefit of the child. Today's condition often happens to mothers or apostates who cause divorce, or the condition of mothers who have divorced their husbands as career women. Does it have implications for hadhanah rights for mothers or fathers? The normative qualitative approach was applied in this study. The results of the discussion of the four cases decided by the Religious Court which became the object of research gave foster rights (hadhanah) to fathers because fathers have competence in child care, such as having good moral, having competence in the science of education and social competence that is responsible and prioritizes the benefit of children from to determine the rights of mothers as child care. In this condition the father fulfills the requirements of the hadhin compared to the mother.